Fish oil blunts lung function decrements induced by acute exposure to ozone in young healthy adults: A randomized trial. (September 2022) - Chen, Hao; Tong, Haiyan; Shen, Wan; Montilla, Tracey S.; Case, Martin W.; Almond, Martha A.; Wells, Heather B.; Alexis, Neil E.; Peden, David B.; Rappold, Ana G.; Diaz-Sanchez, David; Devlin, Robert B.; et al.
Highlights: Acute exposure to O3 induces lung function decrements and airway inflammation. Fish oil supplements blunted O3 – induced lung function effects but not inflammation. Protective effects of olive oil supplements were less pronounced than those of fish oil. OO blunted blood pressure elevations induced by O3 exposure. Beneficial oils have potential as public health interventions against air pollution. Abstract: Background: Over one-third of the U.S. population is exposed to unsafe levels of ozone (O3 ). Dietary supplementation with fish oil (FO) or olive oil (OO) has shown protection against other air pollutants. This study evaluates potential cardiopulmonary benefits of FO or OO supplementation against acute O3 exposure in young healthy adults. Methods: Forty-three participants (26 ± 4 years old; 47% female) were randomized to receive 3 g/day of FO, 3 g/day OO, or no supplementation (CTL) for 4 weeks prior to undergoing 2-hour exposures to filtered air and 300 ppb O3 with intermittent exercise on two consecutive days. Outcome measurements included spirometry, sputum neutrophil percentage, blood markers of inflammation, tissue injury and coagulation, vascular function, and heart rate variability. The effects of dietary supplementation and O3 on these outcomes were evaluated with linear mixed-effect models. Results: Compared with filtered air, O3 exposure decreased FVC, FEV1, and FEV1 /FVC immediately post exposure regardless of supplementation status. Relative to that in the CTL group, the lung function response to O3 exposure in the FO group was blunted, as evidenced by O3 -induced decreases in FEV1 (Normalized CTL −0.40 ± 0.34 L, Normalized FO −0.21 ± 0.27 L) and FEV1 /FVC (Normalized CTL −4.67 ± 5.0 %, Normalized FO −1.4 ± 3.18 %) values that were on average 48% and 70% smaller, respectively. Inflammatory responses measured in the sputum immediately post O3 exposure were not different among the three supplementation groups. Systolic blood pressure elevations 20-h post O3 exposure were blunted by OO supplementation. Conclusion: FO supplementation appears to offer protective effects against lung function decrements caused by acute O3 exposure in healthy adults.